(E)-3-(3, 4, 5-Trimethoxyphenyl)-1-(pyridin-4-yl)prop-2-en-1-one, a heterocyclic chalcone is a potent and selective CYP1A1 inhibitor and cancer chemopreventive agent. Issue 24 (15th December 2017) - Horley, Neill J.; Beresford, Kenneth J.M.; Kaduskar, Supriya; Joshi, Prashant; McCann, Glen J.P.; Ruparelia, Ketan C.; Williams, Ibidapo S.; Gatchie, Linda; Sonawane, Vinay R.; Bharate, Sandip B.; Chaudhuri, Bhabatosh
Graphical abstract: Abstract: The overexpression of CYP1 family of enzymes is reported to be associated with development of human carcinomas. It has been well reported that CYP1A1 specific inhibitors prevents carcinogenesis. Herein, thirteen pyridine-4-yl series of chalcones were synthesized and screened for inhibition of CYP1 isoforms 1A1, 1B1 and 1A2 in Sacchrosomes™ and live human HEK293 cells. The structure-activity relationship analysis indicated that chalcones bearing tri-alkoxy groups (8a and8k ) on non-heterocyclic ring displayed selective inhibition of CYP1A1 enzyme, with IC50 values of 58 and 65 nM, respectively. The 3, 4, 5-trimethoxy substituted derivative8a have shown >10-fold selectivity towards CYP1A1 with respect to other enzymes of the CYP1 sub-family and >100-fold selectivity with respect to CYP2 and CYP3 family of enzymes. The potent and selective CYP1A1 inhibitor8a displayed antagonism of B[ a ]P mediated activation of aromatic hydrocarbon receptor (AhR) in yeast cells, and also protected human cells from CYP1A1-mediated B[ a ]P toxicity in human cells. This potent and selective inhibitor of CYP1A1 enzyme have a potential for development as cancer chemopreventive agent.